Decoupling-Analysis of Ukraine's Economy Regurdingits Sustainable Development - Ivanov, S.V.; Vatchenko, O.B.; Svystun, K.O.; Vatchenko, B.S.; Razumova, H.V. (Science and Innovation, 2024)
Introduction. Timely decoupling analysis of economic growth, environment pressure, and resource consumption in the country enables determining whether it is actually moving towards sustainable development, and how modern and efficient the methods of economic and environment management are in Ukraine. Problem Statement. The existing decoupling studies in Ukraine don’t take into account the impact of economic development on the environment and the resources consumption. Purpose. To make decoupling analysis of Ukraine’s economy by the factors of environment pressure and resources consumption in dynamics for 2013-2017. Materials and Methods. The dialectical method of scientific knowledge, as well as observation, comparison, analytical, and statistical analyses have been used. Results. The study of decoupling factors by the environmental pressures and resource consumption has revealed the absence of a relative decoupling effect in 2013-2017 at the national level, as decoupling factors were unstable and negative in some years. The analysis of the decoupling indices on environmental pressures in the Ukrainian economy has shown that there was a predominantly recessive dependence between economic development and pollution factors in 2013-2015. A negative expansive decoupling was recorded in 2017 between the GDP growth and the rate of unregulated waste water discharge into surface water bodies and the generation of waste of IV hazard class. In 2017, an expansive relation was recorded between GDP growth and aggregate environmental pressure. Also, there was a negative decoupling in the economy of Ukraine between economic development and consumption of fuel resources from wood (overcoupling). Conclusions. The absence of relative decoupling effect in the general dynamics in 2013-2017 by the factors of environment pressure and resource consumption testifies to the existence of significant problems in Ukraine in terms of achieving sustainable development and the necessity of decoupling tool application while forming strategic plans.